Rhizospheric Organic Acids as Biostimulants: Monitoring Feedbacks on Soil Microorganisms and Biochemical Properties - Macias-Benitez, Sandra; Garcia-Martinez, Ana María; Caballero Jimenez, Pablo; Gonzalez, Juan Miguel; Tejada Moral, Manuel; Parrado Rubio, Juan (Frontiers in Plant Science, 2020)
The biostimulant potential of three different organic acids present in the rhizosphere, specifically lactic, oxalic and citric acids, have been studied. The results showed a rapid and complete metabolism of these three acids with soil microorganisms using them as a source of carbon and energy. Biostimulation was confirmed by soil biochemical studies which showed an increase in enzymatic activities, such as dehydrogenase and phosphatase, lactic and citric acids being those that produced the greatest biostimulation. With regard to microbiota composition, amplicon sequencing of the 16S rRNA gene showed changes in the structure of soil microbial communities. Applying organic acids produced a decrease in richness and diversity indices, inducing specific changes in the structure of the microbiological communities. Applying lactic acid induced rapid changes in microbiota composition at both phylum and family taxonomic levels, favouring the proliferation of microorganisms involved in its degradation and soil fertility, such as the genus Bacillus and the family Micrococcaceae. Once the lactic acid was degraded, the biodiversity tended to return to similar phyla, but specific distinctive families and genera remained, leaving a pattern of induction of taxa described as plant growth-promoting bacteria (PGPB), such as the Sinorhizobium and Lysobacter genera, and the Pseudomonaceae family. Similar behaviour was found with citric acid, which favoured the proliferation and dominance of microorganisms of the Clostridiaceae family, involved in its degradation, as well as microorganisms of both the Micrococcaceae and Pseudomonadaceae families which were found on day seven, leaving a similar pattern of induction as that found after the mineralisation of lactic acid. On the other hand, oxalic acid induced long-lasting changes in the bacterial community composition. This was characterised by an increase in the proportion of the Burkholderiales order, which includes microorganisms involved in the degradation of this acid and microorganisms described as PGPB. This study presents evidence supporting the use of organic acids as potential soil fertility inducers, due both to their effects in enhancing the dominance of taxa described as PGPB and to their stimulating soil microbial activity.